Morfología de los Estados Inmaduros y Adulto de Neohydatothrips denigratus (De Santis) (Thysanoptera: Thripidae), con Datos sobre su Biología - Contreras, Eugenia Fernanda (2010)
The adult female of Neohydatothrips denigratus (De Santis) is redescribed, the male and immature stages (larva, prepupa and pupa) are described for the fi rst time, and aspects of the biology of this species are made known. Descriptions of the different stages of development were made from laboratory-reared specimens on using twigs of Phaseolus vulgaris as a feeding and oviposition substrate. Neohydatothrips denigratus undergoes its life cycle on the leaves of P. vulgaris, no immature stages were found in fl owers or fruits. Under controlled conditions (21 ± 2ºC; 80 ± 4% RH; photophase: 12h), this species needed 21.6 ± 1.60 d to complete development (egg: 7.0 ± 1.00 larva I: 3.7 ± 1.40;larva II: 4.2 ± 1.10; prepupa: 1.8 ± 0.70, pupa: 5 ± 1). Longevity was 6.0 ± 2.00 days and observed sex ratio was 2:1. From the sixteen plants belonging to ten families recorded as hosts to this species, larvae were found only on two species of Fabaceae and one of Solanaceae.